Beyond mitotic arrest: the diverse effects of microtubule-targeting drugs on tumor vasculature - April L Risinger (EMBO Molecular Medicine)
For decades microtubule-targeting agents (MTAs) have been a cornerstone of cancer treatment regimens and continue to be heavily employed as backbone chemotherapy in combination with new targeted agents. These drugs include both microtubule stabilizers (e.g. taxanes, ixabepilone) as well as destabilizers (e.g., vinca alkaloids, eribulin). MTAs are commonly referred to as antimitotic drugs based on the rationale that their anticancer efficacy is thought to be primarily due to the cell cycle arrest and subsequent apoptosis of rapidly dividing cancer cells downstream of microtubule disruption. However, accumulating evidence suggests that pharmacological microtubule disruption can also exert profound effects on the tumor microenvironment (TME), particularly through their influence on tumor vasculature and immune infiltration. While several MTAs with distinct binding sites and allosteric effects on microtubule structure are approved for the treatment of various cancers, little is known regarding how these drugs might differentially impact the TME. The recent study by He et al (2025) begins to shed light on these issues by demonstrating that structurally and functionally diverse MTAs can elicit markedly distinct effects on tumor vasculature through a process of pericyte phenotypic switching. These findings support the growing body of literature demonstrating that the antitumor efficacy of MTAs extends beyond their shared antimitotic effects and suggests these drugs could be used in a more rational and targeted manner, particularly as backbone chemotherapy in combination with immunotherapies and other targeted agents.